2011
DOI: 10.1021/om2001662
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite-Driven, Oxorhenium-Catalyzed Deoxydehydration of Glycols

Abstract: Methyltrioxorhenium and perrhennate salts catalyze the deoxydehydration (DODH) of glycols by sulfite, producing olefins regiospecifically. The scope and efficiency of these reactions with respect to the polyol substrate, reducing agent, catalyst, solvents, and various additives are investigated. In general, MeReO3 is a more active catalyst for sulfite-driven DODH, but the Z+ReO4 – derivatives (Z = Na, Bu4N) are more selective. Epoxides are also deoxygenated by Na2SO3/MeReO3, but not by Bu4NReO4. The perrhenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(112 citation statements)
references
References 62 publications
5
106
0
1
Order By: Relevance
“…The thin black lines represent the linear functions that have been fitted to the approximately linear parts of the curves. The dotted line represents the modeled evolution of the alkene concentration according to Equation (9).…”
Section: Changing the Concentration Of The Reductantmentioning
confidence: 99%
See 1 more Smart Citation
“…The thin black lines represent the linear functions that have been fitted to the approximately linear parts of the curves. The dotted line represents the modeled evolution of the alkene concentration according to Equation (9).…”
Section: Changing the Concentration Of The Reductantmentioning
confidence: 99%
“…[51] Although some differences in reactivity have been found upon comparison of CH 3 ReO 3 and various perrhenate salts, they are minor and are presumably the result of different solubilities and beneficial or detrimental effects of the counter ions. Nicholas and co-workers [9] compared CH 3 ReO 3 , NH 4 ReO 4 , NaReO 4 , and Bu 4 NReO 4 in the sulfite-driven DODH of various diols. They concluded that CH 3 ReO 3 was more active than the perrhenate salts, which, however, were more selective, and ascribed the difference in activity between the perrhenate salts to differences in their solubility.…”
mentioning
confidence: 99%
“…In a dried Schlenk tube, Re 2 (CO) 10 (1.0 g, 1.5 mmol) was charged and degassed under vacuum for 30 min, and an excess of 1,2,4-tri(tert-butyl)cyclopentadiene (1 mL, 2 mmol) was added under a nitrogen atmosphere. The resulting mixture was refluxed at 150 8C for 30 min.…”
Section: Synthesis Ofmentioning
confidence: 99%
“…Furthermore, the biomassderived polyols (glycerol and erythritol) were converted into their corresponding olefinic products by 2 as the catalyst. a number of different reductants, including molecular hydrogen, [8] Na 2 SO 3 , [9,10] and alcohols. [11,12] Very recently, independent works by Yi et al [11] as well as Shiramizu and Toste [12] showed the catalytic conversion of polyols into olefins by using MTO and secondary alcohols as both the reductant and solvent.…”
Section: Introductionmentioning
confidence: 99%
“…[1] They eliminate production of organic and inorganic waste side products and the only by-product, hydrogen, is useful as a source of green energy. [15][16][17][18][19][20][21] While there are many examples of homogeneous rhenium deoxygenation catalysts, a limited number of rhenium nanoparticle catalysts have been reported. [1][2][3][4][5][6] Heterogeneous catalysts [7][8][9][10][11][12][13][14] for AD reactions are also highly dependent on the support acting as a base or acid.…”
mentioning
confidence: 99%